EIF VC Survey 2019: Fund managers' market sentiment and policy recommendations - Antonia Botsari; Andrea Crisanti; Frank Lang (European Investment Fund (EIF), 2019)
This working paper presents results of the second EIF VC Survey, a survey among venture capital general partner/management companies. The study provides a detailed overview of the respondents' state of business and market activity as well as their general perception of the European venture capital market, including policy recommendations. In doing so, the study looks at the current situation, developments in the recent past, and expectations for the future.
Keywords: 330